2006
DOI: 10.1002/ijc.21816
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking, elevated fasting serum glucose, and risk of pancreatic cancer in Korean men

Abstract: Pancreatic cancer is one of the most fatal human cancers and continues to be a major unsolved health problem. The goal of this study was to estimate the independent effects and interactions between cigarette smoking and diabetes on the risk of pancreatic cancer in Korean male population. Cigarette smoking and the risk of incidence and death from pancreatic cancer were examined in a 10-year prospective cohort study of 446,407 Korean men aged 40 to 65 years who received health insurance from the National Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 56 publications
4
26
1
Order By: Relevance
“…This was not confirmed by the present study, which indicated an association between mid-BP and glucose levels and risk of pancreatic cancer, whereas the analysis of MetS z-score did not reveal any significant association. Epidemiologic data supports a relationship between obesity and pancreatic cancer (24,25), and between high glucose levels and pancreatic cancer (26)(27)(28), but most studies have reported null associations between cholesterol/hypertension and the risk of pancreatic cancer (29,30). The results in the present study are in accordance with these findings, except that there was no positive association between BMI and pancreatic cancer in men.…”
Section: Discussionsupporting
confidence: 89%
“…This was not confirmed by the present study, which indicated an association between mid-BP and glucose levels and risk of pancreatic cancer, whereas the analysis of MetS z-score did not reveal any significant association. Epidemiologic data supports a relationship between obesity and pancreatic cancer (24,25), and between high glucose levels and pancreatic cancer (26)(27)(28), but most studies have reported null associations between cholesterol/hypertension and the risk of pancreatic cancer (29,30). The results in the present study are in accordance with these findings, except that there was no positive association between BMI and pancreatic cancer in men.…”
Section: Discussionsupporting
confidence: 89%
“…We were unable to exclude the possibility of residual confounding by consumption of alcohol due to a lack of information on alcohol intake within the Asia Pacific Cohort Studies Collaboration. However, several prospective studies have reported that adjustment for alcohol did not materially attenuate the association between smoking and pancreatic cancer (4,32).…”
Section: Discussionmentioning
confidence: 99%
“…The study design and methods for the Korean Cancer Prevention Study have been described in detail previously (17,18). Briefly, the cohort consists of 1,329,525 Korean civil servants and their dependents (846,907 men and 482,618 women) who received health insurance from the Korean Medial Insurance Corporation and who participated in at least one routine biennial medial evaluation between 1992 and 1995.…”
Section: Methodsmentioning
confidence: 99%